Pengaruh Komitmen Organisasi Dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Kantor Badan Pusat Statistik Kabupaten Banggai: The Influence of Organizational Commitment and Job Satisfaction on Employee Performance at the Central Statistics Agency Office of Banggai Regency - Sri Mulyaningsih Kamaru; Suwardi Zakaria; Ichsan Milang; Isti Qomaria Nursin (Jurnal Ilmiah Produktif, 2026)
This study aims to examine the influence of organizational commitment and job satisfaction on employee performance at the Banggai Regency Central Bureau of Statistics Office. Amidst the demands of globalization, employee performance is a major factor for organizational success, so it is important to understand the factors that influence it. A quantitative approach was used by involving all 25 employees as samples. Data were collected through questionnaires, and analyzed using SPSS 27 Software. The results of the regression analysis showed the equation Y = 5.235 + 1.004X1 + 0.168X2. The correlation coefficient value of 0.767 which has a strong level of relationship between variables. The Determination Coefficient value of 0.551 means that the percentage contribution of the influence of the independent variable on the dependent variable is 55.1% and the rest is influenced by other factors outside the study. The t-test shows that organizational commitment has a significant effect with t count 3.735 > t table 2.073 with a probability of 0.001 (<0.025). In contrast, job satisfaction did not have a significant partial effect, with a calculated t of 1.067 < ttable 2.073 with a probability of 0.298 (> 0.025). The F-test obtained a significance of 0.001 (<0.05) with an Fcount of 15.705 > Ftable 3.44, indicating that organizational commitment and job satisfaction jointly have a significant effect on employee performance. These data emphasize the importance of enhancing organizational commitment as a key performance factor while still paying attention to job satisfaction, in order to strengthen employee loyalty and satisfaction through evaluation of compensation and the work environment